IMPLEMENTASI MODEL PEMBELAJARAN INQUIRY TRAINING DALAM PEMBELAJARAN FISIKA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR FORMAL SISWA - Nasution, D.; Mihardi, S. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2015)
Low ability of formal thinking students caused the learning outcomes they get too low. This study aims to determine the effectiveness of the inquiry learning model training in improving students' ability to think formal. The design was used quasi-experimental